КОНЦЕПЦІЯ ПОБУДОВИ СТРУКТУРНО МІНЛИВОЇ ЕЛЕКТРОЕНЕРГЕТИЧНОЇ СИСТЕМИ УКРАЇНИ - Саух, С.Є. (Інститут електродинаміки НАН України, Київ, 2023)
To support the sustainable functioning and development of the energy sector in the conditions of terrorist and military threats, the concept of building a structurally variable electric power system (EPS) is proposed. Structural variability is defined as the ability of the EPS to reproduce such a variety of subsystems and electrical connections between them, which enables the operator to manage the structure of the EPS and, in this way, ensure the stable operation of the electric power industry in conditions of purposeful destructive actions. The concept of a structurally changing EPS is a strategy for anticipating challenges and threats to the sustainable functioning and development of the electric power industry. In order to build a structurally variable EPS, it is proposed to create regional EPSs with their own capacities for production, storage, distribution and supply of electricity in volumes sufficient for consumption by the population, housing and communal services, transport and agriculture within each region. The establishment of the territorial dimensions of individual subsystems, i.e. regional EPS, is determined on the basis of a compromise between the necessary number of such subsystems and connections between them, which ensure the desired degree of variability of the EPS, and the capitalization levels of the regions sufficient to support investment and operating costs for the corresponding regional EPS. It is assumed that the national EPS supports the regional EPS with agreed amounts of maneuvering and reserve capacities and ensures the supply of electricity to enterprises of industrial, construction, transport and other types of economic activity that are of national importance and do not join the regional EPS. In cases of destruction of individual regional power plants, the national power plant, as well as undamaged neighboring regional power plants, together provide the electricity needs of the affected regions. In the structurally variable EPS, uniform rules of behavior of all energy companies as market participants interacting at the national and regional levels should apply. For the organization of such interaction, it is proposed to apply the decomposition of trading platforms and form a distributed electricity market from interconnected upper-level electricity market and regional electricity markets. References 12, figures 6.